The impact of the EU–Vietnam Free Trade Agreement on Vietnamese laws related to climate change - Tin Vo Trung (TalTech Journal of European Studies)
The EU–Vietnam Free Trade Agreement (EVFTA) is considered a historic milestone in the bilateral relationship, particularly in environmental protection. As part of the global trend toward sustainable development, Vietnam must comply with strict environmental regulations under the EVFTA. To honor these commitments, Vietnam is required to reform and enhance its environmental legal frameworks to align with international standards. However, challenges such as gaps between Vietnamese laws and the EVFTA requirements, weak enforcement and balancing economic growth with environmental protection make this challenging. This article critically examines the environmental provisions under the EVFTA, their impact on the Vietnamese environmental legal framework, particularly concerning climate change, and the opportunities and challenges that Vietnam faces in meeting these obligations.